Laminar burning velocity measurements using the Heat Flux method and numerical predictions of iso-octane/ethanol blends for different preheat temperatures. (15th January 2015) - Rau, F.; Hartl, S.; Voss, S.; Still, M.; Hasse, C.; Trimis, D.
Highlights: The laminar burning velocity has been measured with the Heat Flux method. Liquid fuels, namely iso-octane, ethanol and their blends, with air were investigated. With rising ethanol fraction, the laminar burning velocity increases. Measurements are compared to numerical simulations. Simulations cannot predict the exact value but the trend of the burning velocity. Abstract: The substitution of gasoline with bio-ethanol is an intended way to reduce the climate impact of the traffic sector. To extend the knowledge of fundamental flame properties of ethanol/iso-octane flames and improve the numerical predictions for the effect of ethanol blending in internal combustion engines, measurements of the laminar burning velocity of established blend ratios of ethanol and iso-octane were carried out and compared to existing numerical mechanisms. The measurements were carried out with the Heat Flux burner, with thermocouples of type E at the burner plate, which was adapted with an evaporation unit based on direct vaporization to investigate the liquid fuels. The preheating temperature ranges from 298 K to 373 K and the pressure is atmospheric. First measurements of the laminar burning velocity of ethanol/air and iso-octane/air flames were carried out for validating the system. A good agreement with available literature data could be achieved for the investigated equivalence ratios from 0.7 to 1.4. Furthermore laminar burning velocities of different iso-octane/ethanol/air blends, namely E10, E24, E40 and E85, are presented. Through variation of the preheating temperatures (298 K, 323 K, 348 K and 373 K) the temperature dependency could be analyzed. The uncertainty analysis of the measurements has been revealed. Numerical simulations were carried out using different chemical mechanisms for ethanol/air flames, iso-octane/air flames as well as various fuel blends and preheating temperatures and are compared to the experimental data. The agreement is evaluated through a classification of the discrepancy between both.